The Evolving Understanding and Approach to Residual Cardiovascular Risk Management - Dhindsa, Devinder S.; Sandesara, Pratik B.; Shapiro, Michael D.; Wong, Nathan D. (Frontiers in Cardiovascular Medicine, 2020)
Despite unprecedented advances in treatment of atherosclerotic cardiovascular disease, it remains the leading cause of death and disability worldwide. Treatment of major traditional risk factors, including low-density lipoprotein-cholesterol, serves as the foundation of atherosclerotic risk reduction. However, there remains a significant residual risk of cardiovascular events despite optimal risk factor management. Beyond traditional risk factors, other drivers of residual risk have come to the forefront, including inflammatory, pro-thrombotic, and metabolic pathways that contribute to recurrent events and are often unrecognized and not addressed in clinical practice. This review will explore the evidence linking these pathways to atherosclerotic cardiovascular disease and potential future therapeutic options to attenuate residual cardiovascular risk conferred by these pathways.